Behcet's disease concurrent with axial spondyloarthritis: the authors' own observations - Z. S. Alekberova; T. V. Dubinina; R. G. Goloeva; E. M. Agafonova; A. M. Lila (Научно-практическая ревматология)
Objective: to present cases of Behcet's disease (BD) concurrent  with axial spondyloarthritis  (axSpA).Subjects and methods. A total of 470 patients with BD who met the International Standard Bibliographic Description (ISBD) criteria were examined at the V.A. Nasonova Research Institute of Rheumatology in the period from 1990 to2018. In 9 of them, BD was concurrent  with axSpA; 7 out of the 9 patients met the 1984 modified New York criteria for ankylosing spondylitis (AS) and two patients fulfilled the 2009 ASAS non-radiographic axSpA criteria.Results and discussion. Most (55.6%) patients were men. BD was preceded by axSpA in 6 patients. The symptoms of AS joined an average of 8.4 [2; 10] years after the onset of the clinical manifestations of BD. Three patients developed BB 9–15 years after the onset of the first symptoms of axSpA. The mean duration  of BD was 14.0±7.8 years and that of axSpA was 10.9±6.2  years. All the patients were HLA-B27-positive; three were found to have B5 antigen.All the 9 patients had mucocutaneous manifestations  that were characteristic  of BD. Four patients were diagnosedas having eye injuries: generalized uveitis with retinal vasculitis, posterior uveitis with or without retinal vasculitis. Gastrointestinal tract lesions were detected in 44.4% of cases. Peripheral  arthritis was present in all the patients. Entheseal involvement was observed in 66.7% of patients. The radiographic signs of bilateral sacroiliitis according to the modified New York criteria were found in 7 (77.8%) patients; MRI revealed active inflammatory changes in the area of the sacroiliac joint in 3 (33.3%) patients.Conclusion. The fact that there may be an overlap between BD and axSpA should be taken into account in everyday clinical practice, which will assist in choosing the optimal treatment strategy.